Identification of potential dual -targets anti- toxoplasma gondii compounds through structure-based virtual screening and in-vitro studies. - Nurul Hanim Salin; Rahmah Noordin; Belal O Al-Najjar; Ezatul Ezleen Kamarulzaman; Muhammad Hafiznur Yunus; Izzati Zahidah Abdul Karim; Nurul Nadieya Mohd Nasim; Iffah Izzati Zakaria; Habibah A Wahab (PLoS ONE, 2020)
Toxoplasma gondii is the etiologic agent of toxoplasmosis, a disease which can lead to morbidity and mortality of the fetus and immunocompromised individuals. Due to the limited effectiveness or side effects of existing drugs, the search for better drug candidates is still ongoing. In this study, we performed structure-based screening of potential dual-targets inhibitors of active sites of T. gondii drug targets such as uracil phosphoribosyltransferase (UPRTase) and adenosine kinase (AK). First screening of virtual compounds from the National Cancer Institute (NCI) was performed via molecular docking. Subsequently, the hit compounds were tested in-vitro for anti- T. gondii effect using cell viability assay with Vero cells as host to determine cytotoxicity effects and drug selectivities. Clindamycin, as positive control, showed a selectivity index (SI) of 10.9, thus compounds with SI > 10.9 specifically target T. gondii proliferation with no significant effect on the host cells. Good anti- T. gondii effects were observed with NSC77468 (7-ethoxy-4-methyl-6,7-dihydro-5H-thiopyrano[2,3-d]pyrimidin-2-amine) which showed SI values of 25. This study showed that in-silico selection can serve as an effective way to discover potentially potent and selective compounds against T. gondii.